HARGA DIRI ANAK JALANAN DISEKITAR LAMPU MERAH TABEK GADANG KOTA PEKANBARU - Hildayanti, Liana; Rosmawati, Rosmawati; Umari, Tri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: this research was conducted around Tabek Gadang traffic light of Pekanbarucity, the purpose of this research is to determine the characteristics and self-esteem ofstreet children around Tabek gadang traffic light of Pekanbaru city. This research used adescriptive type of research with specified indicators, and data collecting and calculatingmethod with qualitative approach, to obtain the information the researcher takes theinforman in total 6 people, they are street children around Tabek Gadang traffic light ofPekanbaru city. Data collection techniques in this research using interview techniquesand observation. After conducting this research, the results showed that characteristics ofstreet children around Tabek gadang traffic light of Pekanbaru city are varied and thestreet children around Tabek gadang traffic light of Pekanbaru city had a high selfesteem.Key words: characteristics, self-esteem, street children